Pengaruh Metode Pembelajaran Kooperatif Tipe Jigsaw dalam Meningkatkan Minat, Motivasi dan Ketuntasan Belajar Siswa pada Mata Pelajaran Matematika - Mohamad Hamzah (Lembaga Sosial Rumah Indonesia, 2022)
This study aims to increase interest in learning, motivation, and completeness of Class IX-H students of SMP Negeri 1 Kuningan in mathematics. This research includes classroom action research (Classroom Action Research). The research took place at Kuningan 1 Public Middle School with research subjects in class IX-H odd semester 2019/2020 academic year consisting of 35 students. The results of the classroom action research that has been done can be seen that the interest and motivation of students before and after the class action has increased from 27.27% to 65.91% or an increase of 38.64%. This shows that qualitatively it can be said that providing classroom action in the form of a Jigsaw cooperative learning model can increase students' interest and motivation in learning mathematics.